Fusion of Magnetic Resonance Imaging and Real-Time Elastography to Visualize Prostate Cancer: A Prospective Analysis using Whole Mount Sections after Radical Prostatectomy - Brock, M.; Roghmann, F.; Sonntag, C.; Sommerer, F.; Tian, Z.; Löppenberg, B.; Palisaar, R. J.; Noldus, J.; Hanske, J.; von Bodman, C. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To determine whether the fusion of multiparametric magnetic resonance imaging (MRI) with transrectal real-time elastography (RTE) improves the visualization of PCa lesions compared to MRI alone.Materials and Methods: In a prospective setting, 45 patients with biopsy-proven PCa received prostate MRI prior to radical prostatectomy (RP). T2 and diffusion-weighted imaging (T2WI/DW-MRI) and, if applicable, dynamic contrast-enhanced sequences (T2WI/DW/DCE-MRI) were used to perform MRI/RTE fusion. The probability of PCa on MRI was graded according to the PI-RADS score for 12 different prostate sectors per patient. MRI images were fused with RTE to stratify suspicious from non-suspicious sectors. Imaging results were compared to whole mount sections using nonparametrical receiver operating characteristic curves and the area under these curves (AUC).Results: 41 of 45 patients were eligible for final analyses. Histopathology confirmed PCa in 261 (53 %) of 492 prostate sectors. MRI alone provided an AUC of 0.62 (T2WI/DW-MRI) and 0.65 (T2WI/DW/DCE-MRI) to predict PCa and was meaningfully enhanced to 0.75 (T2WI/DW-MRI) and 0.74 (T2WI/DW/DCE-MRI) using MRI/RTE fusion. Sole MRI showed a sensitivity and specificity of 57.9 % and 61 % with the best results for ventral prostate sectors whereas RTE was superior in dorsal and apical sectors. MRI/RTE fusion improved sensitivity and specificity to 65.9 % and 75.3 %, respectively. Additional use of DCE sequences showed a sensitivity and specificity of 65 % and 55.7 % for MRI and 72.1 % and 66 % for MRI/RTE fusion.Conclusion: MRI/RTE fusion provides improved PCa visualization by combining the strength of both imaging techniques in regard to prostate zonal anatomy and thereby might improve future biopsy-guided PCa detection.
Keywords: prostate; ultrasound; MR imaging; treatment planning; staging